Intra-Company Loans in Foreign Direct Investment and Performance of Real Estate Development Projects in Kenya - Sammy Silas Komen Mwaita (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
Foreign Direct Investment has over the years been a critical player in economic growth of mot countries across the globe. One of the key aspects that have defined the success of FDIs is the intra-company loans, which act as a source of affordable, effective and accessible funding to the FDI projects. In Kenya, FDIs have been instrument in economic growth and development, and one of the industries they have been centred on is the real estate development projects. However, very little is known empirically on how FDIs through intra-company loans have contributed to the success of the sector, hence the motivation of this paper. Descriptive research design was used while the target population was the real estate companies in Westlands, Nairobi County. There are forty-eighty registered real estate companies in this area. The units of observation were the directors, finance officers and investment managers from the forty-eight companies. This made a total of one hundred and forty-four respondents. Purposive sampling method was employed where the company directors, finance officers and investment managers were purposively picked. The data was collected using structured questionnaires and analyzed through descriptive and inferential statistical analysis techniques. The findings revealed that intra-company loans significantly and positively influenced the performance of real estate development projects in Westlands Sub-County. Government policy was also found to significantly moderate the relationship between intracompany loans and performance of the real estate development projects. The study concluded that through intra-company loans, the real estate development projects performed better. It is therefore recommended that the real estate development companies through their management embrace FDIs through intra-company loans so as to stir the performance of their development projects.